Volume 1: Turbomachinery 1998
DOI: 10.1115/98-gt-286
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Compressibility and Turbulence Level on Bypass Transition

Abstract: The influences of compressibility and turbulence level on boundary layer transition are studied using a Ludwieg tube set-up. Heat transfer measurements are performed on the flow over a flat plate. The Mach number is varied between 0.16 and 0.56 while the unit-Reynolds number is kept constant. Several turbulence generating grids are used giving turbulence levels between 1.2% and 4.4%. Increasing the Mach number results in a decreasing turbulence level. Besides, the transition start Reynolds number increases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…However, the turbulence level giving a certain distribution is lower in our case (our 1.25% distribution is comparable to Blair's 2% distribution). This also was observed in earlier experiments [17]. It was found that increasing the Mach number results in a decrease of the turbulence level, while no in¯uence on the transition was recognised (when the turbulence grid is unchanged).…”
Section: Transition Experimentssupporting
confidence: 68%
“…However, the turbulence level giving a certain distribution is lower in our case (our 1.25% distribution is comparable to Blair's 2% distribution). This also was observed in earlier experiments [17]. It was found that increasing the Mach number results in a decrease of the turbulence level, while no in¯uence on the transition was recognised (when the turbulence grid is unchanged).…”
Section: Transition Experimentssupporting
confidence: 68%
“…Thus, Narasimha [14] found the effect of Mach number was a delayed transition onset. In contrast, Schook et al [15] found the transition onset Re θ to be consistently lower than that correlated by Mayle [6] for the incompressible range. However, Walsh [13] found reasonably good agreement with the incompressible correlations of Mayle [6] for Mach numbers of the order of 1.…”
Section: Effect Of Mach Numbermentioning
confidence: 69%